2015
DOI: 10.1158/1078-0432.ccr-15-1346
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Validation of Pooled Prognostic Factors in Women with Advanced Cervical Cancer Treated with Chemotherapy with/without Bevacizumab: NRG Oncology/GOG Study

Abstract: Purpose In the randomized phase III trial, Gynecologic Oncology Group protocol 240, the incorporation of bevacizumab with chemotherapy significantly increased overall survival (OS) in women with advanced cervical cancer. A major objective of GOG-240 was to prospectively analyze previously identified pooled clinical prognostic factors known as the Moore criteria. Experimental Design Potential negative factors included black race, performance status 1, pelvic disease, prior cisplatin, and progression-free inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 28 publications
0
43
2
1
Order By: Relevance
“…Importantly, the prospective validation of the Moore clinical criteria 12 in GOG 240 provides oncologists with the first scoring system in cervical cancer which can be used to estimate response and survival and potentially identify patients who are best treated without bevacizumab (e.g., a pre-irradiated patient at risk for fistula for whom the survival benefit attributable to adding bevacizumab is negligible). 17 It should be noted that the late injury of radiotherapy is microvascular and therefore preirradiated patients being considered for treatment with chemotherapy plus bevacizumab should be counseled that the risk of vascular complications may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the prospective validation of the Moore clinical criteria 12 in GOG 240 provides oncologists with the first scoring system in cervical cancer which can be used to estimate response and survival and potentially identify patients who are best treated without bevacizumab (e.g., a pre-irradiated patient at risk for fistula for whom the survival benefit attributable to adding bevacizumab is negligible). 17 It should be noted that the late injury of radiotherapy is microvascular and therefore preirradiated patients being considered for treatment with chemotherapy plus bevacizumab should be counseled that the risk of vascular complications may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the benefit of bevacizumab was greatest in the moderate (2-3 factors) and high-risk (4-5 factors) subgroups (a 5.8-month increase in median OS). However, the survival benefit was small for lowrisk patients (0-1 factor) and toxicity concerns may justify omitting bevacizumab in this case (31).…”
Section: Discussionmentioning
confidence: 81%
“…The structure of both reviews has elements in common with the one presented here and with the proposal found in the Cochrane manual of systematic reviews of interventions [ 38 ]. Other works present validation analyses of prognostic models in patients with early cervical cancer [ 39 ], LACC [ 17 ], and disseminated cancer [ 40 ]. However, only an independent external validation study of 2 predictive models in patients with LACC performed in different population was published [ 24 ].…”
Section: Discussionmentioning
confidence: 99%